Konsep Dasar Belajar dan Pembelajaran dalam Pendidikan - Salsabila Salsabila; Arya Bisma Nugraha; Gusmaneli Gusmaneli (BADAN PENERBIT STIEPARI PRESS, 2024)
Learning is very important to achieve success in the educational process. A good understanding of the basic concepts of learning is very important for educators, such as teachers, instructors, and parties involved in educational units. This research tries to discuss the basic concepts of learning. This basic idea is the starting point for continuing the educational process that produces quality human resources. This type of research is library research using content analysis techniques. This study focuses on several fundamental concepts in education that need to be the foundation and foundation of learning: learning foundations, learning components, learning theories, and learning models.